Informatics in Schools. New Ideas in School Informatics : 12th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2019, Larnaca, Cyprus, November 18-20, 2019, Proceedings /: 12th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2019, Larnaca, Cyprus, November 18-20, 2019, Proceedings. (2019) - Unknown
No abstract available